Antimicrobial Resistance Pattern in Two Intensive Care Units in A Resource Limited Setting. (March 2022) - Oladele, R.; Akanmu, L.; Adeleke, G.; Ettu, A.W.; Adetifa, K.; Peters, C.; Njagua, E.N.; Ogunsola, F.
Abstract : Purpose: Antimicrobial resistance (AMR) is a major determinant of outcome for patients in the intensive care unit (ICU). Susceptibility data derived from surveillance can be a barometer for emerging resistance. This study determined the rates of ICU acquired infections, clinical outcome, and antimicrobial resistance pattern of pathogens causing these infections in in a low resource setting. Methods & Materials: This was a 6-month prospective cohort study in 2 ICUs in Nigeria. Patients were recruited and followed-up until they were either discharged from the ICU or died. Sociodemographic and clinical data was obtained from each patient. Relevant clinical specimens were collected aseptically and processed accordingly. All pathogens isolated were identified using vitek 2. Primary outcome was ICU discharge or mortality. Results: One hundred and five patients were recruited; 73(69.5%) had clinical features suggestive of infection and 140 samples were collected and processed. ICU infection rate was 52.1% (38/73). 71(97.3%) had antibiotherapy; commonly used were Ceftriaxone and metronidazole (30), followed by Meropenem (26). 16(44.4%) had more than one infection, and a total of 90 different infections were documented. Blood stream Infection was 37%, Urinary tract infection was 31.5%, Respiratory tract infection was 6.9% and Soft Skin and tissue infection was 4.1%. Candida species 21.2%, Klebsiella pneumonia 18.9%, Acinetobacter baumannii 15.6% were the most predominate pathogens. Multidrug resistant (MDR) gram-negative organisms accounted for 72.9% (43) of the pathogens. 17 isolates of Klebsiella pneumonia and 10 isolates of Acinetobacter baumannii were MDR. Five of the Klebsiella pneumonia were ESBLs producers. High level of resistance was found against Cefazolin with only 2 isolate showing susceptibility and cabapenem resistance was 64%(34) among gram negative organisms with 64% been observed among Klebsiella spp and Acinetobacter spp . No Methicillin resistant Staphylococcus (MRSA) was isolated. Crude mortality rate was 50.7% (37/73); 10 of whom had gram-negative bacteraemia, 8 of which were MDR. Conclusion: We documented high AMR rates in a resource limited setting, where patients pay from pocket for ICU care. A robust antimicrobial stewardship program with educational intervention is critical to combat this problem.